Association of MAPT subhaplotypes with clinical and demographic features in Parkinson’s disease - Deutschlander, Angela B. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: To determine whether distinct microtubule‐associated protein tau MAPT H1 subhaplotypes are associated with clinical and demographic features in Parkinson’s disease. METHODS: A retrospective cohort study included 855 unrelated Caucasian patients with Parkinson’s disease who were seen by Movement Disorder specialists at the Mayo Clinic Florida between 1998 and 2016. The primary outcome measures were specific demographic and clinical features of Parkinson’s disease, including age at onset, disease progression, survival, motor signs, dementia, dystonia, dyskinesia, autonomic dysfunction, impulse control disorder, psychiatric features, REM sleep behavior disorder, restless legs syndrome, and Parkinson’s disease subtype. Specific clinical features were measured at the initial visit and most recent visit. These outcomes were assessed for association with MAPT H1 subhaplotypes, which were defined by six haplotype tagging variants. RESULTS: Median onset age was 64 years (range: 22‐94 years); 548 (64%) of patients were male. Significant associations (P < 0.0029) were observed between MAPT H1b and orthostatic hypotension (OR = 1.72, P = 0.001); between H1j and rest tremor (OR = 0.15; P < 0.001) as well as REM sleep behavior disorder (OR = 3.87, P < 0.001); between H1r and bradykinesia (OR = 0.11; P < 0.001); and between H1v and restless legs syndrome (OR = 4.02, P = 0.002). INTERPRETATION: Four MAPT H1 subhaplotypes, but not the H2 haplotype, were significantly associated with specific clinical features in Parkinson’s disease. MAPT haplotypic structure may explain some of the phenotypic variability in disease. Replication of our findings will be critical to fully resolve the Parkinson’s disease risk association signal at Chr17q21.